Six new records of Lamiaceae for Bangladesh - Khanam, Mahbuba; Khan, Md Salar; Hassan, Md Abul (Bangladesh Journal of Plant Taxonomy, 2003)
No abstract available. Bangladesh J. Plant Taxon. 10(1): 35-40, 2003 (June)